Registration of the canonical marriage celebrated in Spain between a Spanish national and a Lithuanian woman residing abroad. Reflections on the resolution (16th) of the Directorate General of Registries and Notaries of 14 November 2019 - Gluhaia, Diana (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
The Resolution of the DGRN of 14 November deals with the question of access to the Spanish Civil Register of the canonical marriage celebrated in Spain between a Spaniard and a Lithuanian, both domiciled in London. The DGRN accepts the registration in the Civil Register based on the Agreement between the Spanish State and the Holy See on legal matters.
Keywords: canonical marriage; ecclesiastical certification; wedding celebrated in Spain between Spaniard and foreigner; Spanish Civil Registry